Prognostic value of handgrip strength and functional indicators in elderly patients in a southern brazilian hospital - Kock, Kelser de Souza; Santos, Halen D’Aquino Claudio (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: the handgrip strength (HGS) is an important functional indicator in the elderly. The aim of this work was to evaluate the prognostic value of HGS, sociodemographic and functional indicators in elderly patients in a hospital in southern Brazil. Methods: prospective cohort observational study in individuals aged 60 years or older who were admitted to the clinical sectors in a tertiary Hospital of a southern Brazil. Results: a total of 218 participants were evaluated, of which 55% were men, with median age (p25-p75) of 72 years (65.7-78.0). The most prevalent hospitalization diagnoses were respiratory (19.7%) and vascular (19.3%) disorders. The median values (p25-p75) of HGS for men and women were, respectively, 50.00 (25.0-65.0) and 30.0 (20.0-40.0) kgf. As to the outcome, 44 (20.2%) individuals eventually died. The study showed that there was higher chance of mortality in aged patients (OR = 1.063; CI 95% 1.021-1.108) with higher Charlson Comorbidity Index scores (OR = 1.293; CI 95% 1.149-1.256), Glasgow Coma Scale Index scores <15 (OR = 15.656; CI 95% 7.161-34.228), Katz Index scores <6 (OR = 15.617; CI 95% 6.496-37.545), laboratory tests indicating leukocytosis (OR = 4.118; CI 95% 1.984-8.546) and anemia (OR = 3.104; CI 95% 1.307-7.369), lower HGS values (Men: OR = 0.901; CI 95% 0.862-0.941; Women: OR = 0.926; CI 95% 0.896-0.956), and longer length of stay in hospital (OR = 1.088; CI 95% 1.042-1.136). Conclusion: HGS and other epidemiological indicators are highly relevant in the prognostic evaluation of elderly people in hospital admission.